THE INFLUENCE OF STUDENTS’ PERCEPTION ON SOCIAL INFORMATION SERVICES AND INDEPENDENCE TO SELF ADJUSTMENT - Kholiq, Abdul; Sugiyo, Sugiyo; Saraswati, Sinta (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2016)
Abstract The phenomenon that occurs is the seventh grade students of SMP N 22 Semarang has an average adaptability 70%, while the services of social information has been provided by the teacher of guidance and counseling regularly. In addition there is a significant difference in the level of student independence. The purpose of this study is to determine and analyze the influence of students' perception on social information services and independence to self adjustment seventh grade students of SMP N 22 Semarang. This research is an ex post facto with quantitative approach. The study population numbered 240 students sample taken by purposive sampling technique. Collecting data using psychological scale were tested for its validity and reliability. The data analysis used is simple and multiple linear regression. The results are (1) Perceptions of students on social information services influences self adjustment, (2) Independence influences self adjustment, and (3) Perceptions of students on social information services and independence influences self adjustment. Based on these results it can be predicted that the higher level of students' perceptions on the service of social information and independence, the adaptability of students will be increased. Therefore, it is suggested that teachers of guidance and counseling should provide services that fit the needs of students so that students have a better perception on social information services and also they should foster students' independence.